Circulating adipose-tissue miRNAs in gastrointestinal cancer patients and their association with the level and type of adiposity at body composition analysis - Tambaro, Federica; Imbimbo, Giovanni; Pace, Valentina; Amabile, Maria Ida; Rizzo, Veronica; Orlando, Simona; Lauteri, Giulia; Ramaccini, Cesarina; Catalano, Carlo; Nigri, Giuseppe; Muscaritoli, Maurizio; Molfino, Alessio (Frontiers in Molecular Biosciences, 2024)
Background: Adipose tissue (AT) wasting in cancer is an early catabolic event with negative impact on outcomes. Circulating miRNAs may promote body weight loss and cachexia. We measured circulating miRNAs linked to AT alterations and compared their levels between i) gastrointestinal (GI) cancer patients and controls, ii) cachectic and non-cachectic cancer patients, and iii) according to adiposity level and its distribution.Methods: Patients with GI cancer and subjects with benign diseases as controls were considered. Cachexia was assessed and adiposity evaluated by CT-scan for subcutaneous AT area (SAT), visceral AT area and the total AT area (TAT). MiRNAs involved were measured in plasma by RT-qPCR.Results: 37 naïve GI cancer patients and 14 controls were enrolled. Patients with cachexia presented with lower SAT compared to non-cachectic (p<0.05). In cancer patients, we found higher levels of miR-26a, miR-128, miR-155 and miR-181a vs controls (p<0.05). Cancer patients with BMI<25 kg/m 2 showed higher levels of miR-26a vs those with BMI≥25 (p=0.035). MiR-26a and miR-181a were higher in cachectic and non-cachectic vs controls (p<0.05). Differences between cachectic and controls were confirmed for miR-155 (p<0.001) but not between non-cachectic vs control (p=0.072). MiR-155 was higher in cachectic patients with low TAT vs those without cachexia and high TAT (p=0.036).Our data confirm a modulation of specific and different miRNAs involved in AT metabolism in cancer and cachexia. MiR-155 levels were higher in patients presenting with cachexia and low adiposity with implications in the pathogenic mechanisms and clinical consequences of GI cancer patients.